VD_FINDINFO Jug / 2014 / 356 vom 23. Oktober 2012 - VD Tribunal cantonal (2012)
EMPLOYÉ PUBLIC, INTERDICTION DE L'ARBITRAIRE, ÉGALITÉ DE TRAITEMENT, DROIT D'ÊTRE ENTENDU | 29 al. 2 Cst., 8 al. 1 Cst., 9 Cst., 23 LPers-VD